A comparative quality study of saffron constituents through HPLC and HPTLC methods followed by isolation of crocins and picrocrocin. (October 2017) - Kabiri, Maryam; Rezadoost, Hassan; Ghassempour, Alireza
Abstract: Saffron ( Crocus sativus L.) is a precious commodity with a high economic value for exporting countries such Iran. One of the major challenges of saffron cultivation is the lack of a reliable method of saffron secondary metabolites determination. This study is aimed to introduce a reliable and accurate method for determining the quality of saffron. In the proposed method, a semi-preparative HPLC was optimized for isolation and purification of crocins and picrocrocin from Saffron extract. To ensure the accuracy of purified compounds, their structure was confirmed by HPLC-DAD-MS. Thereafter two common analytical methods were developed and validated, HPLC-DAD and HPTLC-DAD. The results of these two methods were compared with the aim of finding more accurate analytical method. Next, the obtained results were compared to results of ISO 3632 method. Since crocins and crocetin both have absorbance at maximum wavelength along with other of Saffron constitutes including safranal and picrocrocin, there is an overestimation in HPTLC and ISO 3632 in comparison with HPLC-DAD. The simultaneous comparison of these three analysis methods and the isolation of picrocrocin and crocins, for the first time are done in this study. Eventually HPLC, in both preparative and analytical scale, was recommended to determine Saffron quality. Highlights: Drawback of ISO 3632 spectrophotometric method for saffron quality determination. Why and how it is impossible to use crocins from other crocins containing sources such Gardenia jasminoides . Introducing semi-preparative HPLC as reliable method of saffron main constitutes preparation. Introducing a novel comparison study of three common methods for quality determination saffron.